Strategi Dakwah Digital Ustadz Abdul Somad: Sintesis Literatur tentang Strategi Konten, Multiplatform, dan Keterlibatan Audiens - Rhohis Kurniawan; Syahrizal; Canra Krisna Jaya (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
The effectiveness of Islamic religious propagation in the digital era requires adaptive and measurable communication strategies. This research aims to analyze Ustadz Abdul Somad's preaching strategy in enhancing the effectiveness of religious propagation through digital media utilization. The research method uses a qualitative approach with library research on various scientific literature, academic articles, and digital documentation. The results show that Ustadz Abdul Somad implements five main strategies: (1) content segmentation based on audience needs, (2) optimization of social media platform algorithms, (3) personalization of communication style with simple and contextual language, (4) consistency of content publication schedule, and (5) building two-way interaction with the audience. The effectiveness of the strategy is proven by high engagement rates and reach of millions of followers across platforms. The contribution of this research provides a digital preaching strategy model that can be adopted by preachers in optimizing religious propagation in the digital era